Suggestions on the implementation of the special planning of rural teaching network -Taking Xiushui County as an example. (August 2020) - Sun, Hailan; Fan, Meng; Liao, Jiayi; Yang, Qing
Abstract: The report of the 19th National Congress of the Communist Party of China puts forward "giving priority to the development of education". Building a strong education country is a basic project for the great rejuvenation of the Chinese nation. We must give priority to the cause of education, speed up the modernization of education, and run education to the satisfaction of the people. The planning of rural teaching network in Xiushui county is of great significance to other rural areas in China. In order to speed up the solution to the current problems of "difficulty in entering the kindergarten" of preschool education in Xiushui County, the problems of "large school size" and "large class size" of primary and secondary schools, improve the layout of campus, promote the healthy and sustainable development of basic education, and promote the integrated development of urban and rural education as a whole, this project is carried out in accordance with the unified layout of Xiushui county Party committee and government, and in accordance with the planning requirements of education development, urban and rural planning and other industries suggestions for implementation are prepared.